Monocytes as a diagnostic marker of cardiovascular diseases - Gratchev, Alexei; Kzhyshkowska, Julia (Immunobiology, 2012)
Inflammation is an important pathogenic factor of cardiovascular diseases. Inflammatory processes induce the organism systemic changes that are sensed by the cells of innate immune system. These systemic changes include increased concentrations of soluble factors capable of activating monocytes in the blood circulation therefore monocytes represent highly attractive cell population for diagnostic use. To date various parameters of circulating monocytes were associated with cardiovascular diseases. These comprise monocyte count, increased adhesive properties, alteration of lipid metabolism, phagocytosis and endocytosis of LDL. Search for markers, better suitable for clinical use led to identification of monocyte population heterogeneity. One of the best studied markers for identification of monocyte subpopulation is CD16. Although there is no consensus regarding the origin and composition of various monocyte subpopulations, association of increased size of CD16+ monocyte population with atherosclerosis is well established. Further surface markers of monocytes found to be associated with cardiovascular diseases are CD18, CD11b, CXCR1, CD36 and STAB1. Functional studies performed on primary human monocytes support the importance of these molecules for the pathogenesis of cardiovascular diseases. Continuous research on monocyte biology leads to identification of perspective markers that show significant potential of clinical use. These include analysis of monocyte response to a challenge and level of mitochondrial DNA heteroplasmy. Further research involving genomic, proteomic and cell biology techniques supplemented with systems biology approaches for data analysis and computer simulations are required for defining molecular and functional parameters of monocytes to be used as a diagnostic tool or therapeutic target.
Gesehen am 03.05.2018